Sistem Zonasi Penerimaan Peserta Didik Baru dan Dampaknya terhadap Hasil Belajar Bidang Studi Pendidikan Agama Islam di SMP 1 Lubuk Sikaping - Khairil Aftar; Ahmad Lahmi; Rahmi (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
The ZoninggSystem forrNew Student AdmissionssPolicy is contained in the Regulation of theeMinister offEducation anddCulture Numberr17 of 2017 concerninggthe Admission of New Students. It issexpected to beea solutionnto achieveeeducational equality. But unfortunately,tthis policy received many complaintssfrom variouspparties, especiallyyfrom parentsoof high achieving students.TThis studyyaims to determineethe impactoof the Student Admissions Zoning System (PPDB) ontthe Achievements and LearninggOutcomes of Students'”Islamic Education at SMP Negeri 1 Lubuk Sikaping. The research method in this research is to use a descriptiveeresearch method withaa qualitative approach..This studyuuses the comparativeeafter only indicator to determine the impact offthe implementationnof theeZoning System PPDB policy. Theeresults offthis studyyare, theepositive impactoof PPDB zoninggsystem istthe existenceoof equitableeeducation, and eliminatingsschool discrimination..The negativeeimpact is theegathering of studentsswith differentaabilities innone class, this condition makes reducing interest in learning. Teachers find it difficult to teach because in the classroom, they do not only consist of high-achieving students as before,rresulting in decreased schoolpperformance, less communicativeelearningaactivities, and decreased schoolqquality. Meanwhile, the factor that becomes an obstacleein implementinggthe PPDBppolicy on this zoning system; there are nothing good regulations regardinggthe implementation offthe policy.TThe policy issnot accompanieddby an increaseein the quality and quality of education,pprovision of educational facilities, and training of competent educators in all schools